2018
DOI: 10.1177/1533033818798633
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Literature Review on Salvage Radiotherapy for Local or Regional Recurrence After Previous Stereotactic Body Radiotherapy for Lung Cancer

Abstract: Purpose:The purpose of this review article was to summarize available data on the efficacy and safety of salvage radiotherapy for isolated local or regional recurrence after prior stereotactic body radiotherapy for lung cancer.Methods:Studies were systematically searched on PubMed, following which suitable papers were selected. Reported outcomes and toxicities were qualitatively reviewed.Results:Nineteen papers, which were retrospective studies based on single institution experiences, were selected. Sixteen pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
(83 reference statements)
0
7
0
Order By: Relevance
“…An early diagnosis of lung cancer relapse is essential, as in some cases, a curative intended treatment might be feasible [ 1 ]. In this study, relapsed lesions within HDV had higher FDG-SUV peak and larger MTV, than the relapsed lesions outside of HDV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An early diagnosis of lung cancer relapse is essential, as in some cases, a curative intended treatment might be feasible [ 1 ]. In this study, relapsed lesions within HDV had higher FDG-SUV peak and larger MTV, than the relapsed lesions outside of HDV.…”
Section: Discussionmentioning
confidence: 99%
“…The early and precise diagnosis in patients suspected for lung cancer relapse is essential, as a curative intended treatment might be feasible [ 1 ]. The 2-deoxy-2-[ 18 F]fluoro- d -glucose (FDG)-PET/CT is recommended in patients with a clinical suspicion of recurrence of lung cancer after treatment [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Re-RT can be instilled in almost all in-field local recurrent tumors, such as the brain [ 8 , 9 ], head and neck [ 10 , 11 ], lungs [ 12 ], breast [ 13 ], abdomen [ 14 ], pelvis, prostate and gynecological regions [ 15–18 ], bone [ 19 ] or secondary primary cancers [ 10 ]. We know that the patterns of disease progression and prognosis are largely dependent on the site and cancer histopathology.…”
Section: Discussionmentioning
confidence: 99%
“…For centrally located lung tumors or nodal recurrences after previous irradiation, some authors have discouraged the use of SABR because of the perceived high risks of toxicity. 16,17 In other studies that included central lesions without prior radiotherapy, a higher rate of grade 5 toxicities was often reported. [16][17][18] In an analysis of 32 lesions (11 central) that were previously irradiated, Peulen et al reported that treatment of central lung lesions and lesions with larger volumes resulted in higher toxicity; 9 of 29 patients had grade 3 or higher toxicity, including 3 cases of fatal hemoptysis.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 In other studies that included central lesions without prior radiotherapy, a higher rate of grade 5 toxicities was often reported. [16][17][18] In an analysis of 32 lesions (11 central) that were previously irradiated, Peulen et al reported that treatment of central lung lesions and lesions with larger volumes resulted in higher toxicity; 9 of 29 patients had grade 3 or higher toxicity, including 3 cases of fatal hemoptysis. 17 Another prospective trial studying salvage SABR in NSCLC did not include any central lesions in their reirradiation series.…”
Section: Discussionmentioning
confidence: 99%